VIVER, CONVIVER, TRABALHAR: TRAJETÓRIAS DE TRABALHO E SOCIABILIDADE NO DISTRITO DO ITAIACOCA, PONTA GROSSA PR - (1970-2014) - Koslosky, Matheus (2016)
This essay aims at investigate how labor, the sociability and country life were experienced by men and women who lived from subsistence farming in Itaiacoca’s District, a Ponta Grossa’s county, in Paraná state, since 1970 to 2014, a period in which important social transformations occurred on small and medium ranchers from that district. For this, I started studying the aspects of Paraná’s countryside constitution, specially Itaiacoca’s ones, between 1970 and 1990, which allowed me to understand the workers’ experienced historical processes, trying to analyze relevant issues related to identities and memories of these people. The dissertation discuss the constructed senses of these historical subjects about the way of living, laboring and residing in Itaiacoca’s District, as well as how they think about the meaning of “being an itaiacocano”, dialoguing with the emerging memories upon the researched process.